Selected Issues Related to Electronic Medical Records (EMR) (Discourse of Law and Administration, 2024)
The article examines issues related to electronic medical records (EMR), particularly the differences between medical records in electronic form and EMR, and the legal and technical regulations concerning these matters. It discusses the development of the EMR definition in Polish law, highlighting the role of the P1 System in its functioning and the obligations of medical entities regarding the maintenance of electronic records. The article emphasizes the benefits of EMR, such as increased efficiency and accessibility of medical data, and identifies technical and organizational challenges that hinder its full implementation. The conclusions include recommendations for better use of IT tools in healthcare and eliminating hybrid documentation practices, which lead to data inconsistency.
Keywords: Electronic medical records; health care system; modern state; quality of health care system